A Fast Encoding Algorithm for BCH Codes Based on Constructing Array Table - Zhang, Huanming; Zhou, Yuexia; Xiao, Yonghao (2025 21st International Conference on Natural Computation, Fuzzy Systems and Knowledge Discovery (ICNC-FSKD), 2025)
Cyclic codes, which have been widely used in modern communication systems, can be constructed over finite fields. BCH codes are a subclass of cyclic codes with many special properties that enable efficient encoding and decoding. This paper presents an array table of natural numbers to implement encoding of BCH codes through linear operations.